Tuberculosis Extra Pulmonary Bacilli Detection System Based on Ziehl Neelsen Images with Segmentation - Bob Subhan Riza; Jufriadif Na'am; Sumijan Sumijan (Universitas Bumigora, 2022)
Tuberculosis Extra Pulmonary (TBEP) is one of the infectious diseases that can cause death. The bacterium Mycobacterium tuberculosis is the cause of this disease. Patients suffering from this disease must be treated quickly. Currently, patients need a long time and a large cost in detecting the bacteria that cause this disease. The technique used is to take the patient's lung fluid by biopsy and given Ziehl Neelsen chemical dye and then observed using a microscope. This study aims to help detect bacteria quickly and precisely by processing the image produced by the microscope. The technique used is to develop the segmentation method. The segmentation process carried out is to develop a Hue Saturation Value (HSV) color space transformation technique with Active Contour, Edge Detection, and Otsu techniques. The images used in this research are 51 images taken from H. Adam Malik Hospital, Medan and have been validated by an expert. Of the several segmentation methods used in this study, the maximum or best result in detecting Tuberculosis Extra Pulmonary (TBEP) bacilli is the Otsu method. So the method developed is very helpful in accelerating the detection of TBEP.